FINANCING, MARKETING, AND DIGITALIZATION SOLUTIONS FOR MSMEs IN THE NEW NORMAL ERA - Sopi Pentana (Jurnal Ekonomi, 2023)
The Covid-19 pandemic has not only had an impact on the health sector which has resulted in fatalities, but has also had an impact on the economic sector and the level of people's welfare. The middle to lower middle class people are experiencing difficulties due to the Covid-19 pandemic, they cannot work as they should, there are even companies that have been forced to carry out mass termination of employment (PHK) because they are no longer able to pay employee salaries if they have to maintain their jobs. employees with working conditions or rules that are currently being implemented. In Indonesia, the government is currently trying to keep pushing the economy to keep moving despite the decline. Many MSME businesses have started to experience a drastic decline in sales or even have no customers at all because customers have started doing activities in their respective homes. However, the continuity of the MSME business must be carried out so that the business can be maintained. The results obtained are in the first model, there are 2 variables that are proven to be significant, namely banking variables and cooperative variables that have an effect on payments, in the second model, all variables are proven to be significant, namely HR variables, competitor variables and innovation variables that have an effect on marketing. Furthermore, in the third model, all variables were proven to be significant, namely technology variables, internet variables and packaging & design variables that had an effect on digitalization.